Women Health and Menstrual Hygiene Management in Natural Disasters: A Study in Islampur Upazila of Jamalpur District (Journal of the Asiatic Society of Bangladesh, Science, 2017)
The study examines health and menstrual hygiene management of disaster affected women at Kulkandi Village under Islampur Upazila of Jamalpur District and explores their needs and problems regarding menstrual hygiene issues during disasters. This present study based mainly on primary field investigation including questionnaire survey with women and girls, focus group discussions (FGDs) and key informant interviews (KIIs) reveals that unhygienic sanitation and unclean water during disaster leads them to severe health issues including gynaecological problems. A significant number of respondents (21%) experienced urinary tract infections and 24% faced rashes on sensitive private parts of their bodies. Managing their menstruation and maintaining a good standard of menstrual hygiene is difficult for them because of the factors established in this study, such as inadequate knowledge, culture and traditions, inadequate facilities and services, poverty and lack of access to health care. Effective cooperation from both the government agencies and NGOs is needed to promote good menstrual hygiene management (health care issues, sanitary pads in relief materials, workshops) in the studyAsiat. Soc. Bangladesh, Sci. 43(1): 83-99, June 2017